PRE-DONATION SCREENING OF VOLUNTEER PRISONER BLOOD DONORS FOR HEPATITIS B & C IN PRISONS OF PUNJAB, PAKISTAN - Pervaiz, Aslam; Sipra, Fateh Sher; Rana, Tanveer Hussain; Qadeer, Imran (Journal of Ayub Medical College Abbottabad, 2015)
Background: Prisoners as a high risk group are never recommended for blood donations. In Pakistan, prisoners are legally allowed to donate blood and get thirty days extra remission. Inspectorate of prisons allowed Alizaib Foundation for blood donation camps subject to pre-donation screening of volunteer prisoner blood donor against infectious diseases. This study was conducted to identify the potential benefits of pre-donation screening. Methods: This cross sectional study was conducted in October, 2009 in Punjab. Intending volunteer prisoner blood donors from January, 2007 to September, 2009 from prisons of Punjab were included. Physically fit were tested for Hepatitis C Virus (HCV) and B Virus (HBV) by Rapid test kit before bleeding. Data was analysed by Epi-Info. Results: A total of 5894 male volunteer prisoner donors were screened and 1038 (17.6%) were rejected. The mean age was 28 years (range: 17-70 years). Of 5894, 857 (14.5%) were HCV positive and 222 (3.8%) were HBV positive. HCV & HBV co-infection was present among 41 (0.7%). Being convicted prisoner blood donor is significantly associated with higher seroprevalence for HCV (OR 1.35, 95% C.I. 1.17-1.57) and being under trial prisoner is significantly associated with higher seroprevalence for HBV (OR 1.40, 95% C.I. 1.06-1.85). Conclusion: Hepatitis B & C viruses were responsible for almost 18% prisoner blood donor rejection. Pre-donation screening of blood donors is an effective intervention to improve the safety and limit the cost of blood. Treatment of identified cases may contribute to public health. In the international scenario this study findings necessitate the amendments in the relevant prison rules.